Kemandirian Santri: Strategi Pendidikan Tradisional Pondok Pesantren - Johariah, St. Johariah; Wahid, Abdul (Program Pascasarjana Universitas Muslim Indonesia, 2024)
This research originated from issues related to student freedom within the educational organization journey. Firstly, the emergence of a learning freedom crisis, particularly in conventional institutions. Secondly, the teaching system in schools does not guarantee the regulation of student freedom in accordance with the goals of general education. This study aims to explore the methodology of Islamic live-in schools in shaping the independence of Khairul Ummah students in Bantaeng Regency, as well as identifying variables that support or hinder student independence. The research involved subjective examinations at the Islamic Life Experience School Khairul Ummah, Bantaeng Regency. The information collection methods used included perception techniques, meetings, and documentation. Examination procedures included information collection, reduction, display, and inference. The results of the study showed that Islamic boarding schools implement several strategies to foster student independence, including setting examples, recommendations, and mentoring. These strategies result in independence such as initiative, confidence, and responsibility. Supporting factors for independence include system support, cooperation among students, mentors, teachers, administrators, and parents, as well as parental trust and support. Meanwhile, inhibiting factors include communication with parents, the disconnect between the efforts of boarding schools and parents, and diverse student backgrounds. The conclusion of this research is that the methodology used by the Islamic Life Experience School Khairul Ummah, Bantaeng Regency, in fostering student independence is by providing examples, recommendations, and mentoring